The Effect of Mergers and Acquisitions on the Financial Performance Companies listed on the Indonesia Stock Exchange for the 2020-2022 period - Nadya Salsabila; Maya Sari (Jurnal Syntax Admiration, 2024)
This research aims to determine the effect of mergers and acquisitions on company financial performance in companies listed on the Indonesia Stock Exchange. The data collection method used in this research is a purposive sampling technique, based on existing criteria, there are 30 sample companies. The company's financial performance is measured using financial ratios, namely: Return On Assets (ROA), Current Ratio (CR) and Debt To Asset Ratio (DAR). The analytical method used in this research is the T-test difference analysis and the Wilcoxon signed rank test. The research results show that companies that carry out mergers and acquisitions in 2020-2022 with an average period of 1 year before and 1 year after the merger and acquisition show that there is no difference in profitability as indicated by Return On Assets (ROA), liquidity as indicated by Current Ratio (CR), solvency shown by Debt To Asset Ratio (DAR), before and after mergers and acquisitions. This research was conducted incompanies that carry out mergers and acquisitions in 2020-2022 and are listed on the Indonesian Stock Exchange. This study provides an in-depth understanding of how mergers and acquisitions affect the financial performance of companies in the Indonesian capital market. Therefore, stakeholders such as investors, company managers, regulators and academics can gain a better understanding of the impact of merger and acquisition activities on the Indonesian economy. There has been no research regarding the effect of mergers and acquisitions on financial performance in the 2020-2022 period in Indonesia. This knowledge gap is the reason for conducting this research.